Unusual dislocation behavior in high-entropy alloys. (May 2020) - Ma, Evan
Abstract: This Viewpoint article articulates ten unusual features associated with dislocations and their slip processes in high-entropy alloys (HEAs). Attention will be directed towards the composition undulation almost inevitable in these highly concentrated solutions, even when the alloy is a single-phase and nominally random solution. This inhomogeneity is often exacerbated by lattice distortion and local chemical order arising from the interaction among multiple principal elements. As a consequence, dislocation motion faces a rugged atomic and energy landscape, presenting new twists in defect energetics and properties, as well as cocktail strengthening as a new form of solid solution hardening beyond the conventional mechanism. Our systematic account from this standpoint may help answer the continual query in the community as to what is special about these HEAs that makes them different from traditional solid solutions. Graphical abstract: A dislocation moving in a face-centered-cubic high-entropy alloy. Image, graphical abstract